A psychodynamic understanding of obsessive compulsive disorder - Ning, Xin Gan; Nuruddin, Arlina; Jin, Kiat Ang (OASK Publishers, 2024)
Obsessive Compulsive Disorder, (OCD) is characterized by obsession and/ or compulsion that lead to significant distress with functional impairment. Psychodynamic formulation is commonly used to understand the patient’s unmet needs and could guide management plan. Psychodynamic psychotherapy is not the mainstay psychological treatment for OCD. Nevertheless, psychodynamic understandings are crucial to understanding the formulation of symptom. This case report illustrates a patient who is suffering from OCD which originated from his unresolved fixation in psychosexual anal stage, harsh superego, neurotic defense mechanisms of undoing and isolation of affect, and insecure attachment worsened during the COVID-19 pandemic. Psychodynamic issues should be explored for a more comprehensive psychosocial intervention, better therapeutic alliance and treatment outcome.